Diagnóstico da arborização urbana da Vila Brasília, Serra do Mel, RN, Brasil - Maria Dayanne Vieira; Lucas Emanuel Marinheiro de Oliveira; Luiz Tavernard de Souza Neto; Diego Nathan do Nascimento Souza (Terr@ Plural)
The late and accelerated urbanization initiated in the 20th century has triggered social and environmental impacts in the cities, caused by soil paving, suppression of arboreal vegetation, heat islands and loss of floristic biodiversity. The present work aims to carry out a diagnosis and promote a discussion that subsidizes the planning of urban afforestation in Vila Brasília, in the city of Serra do Mel, located in the state of Rio Grande do Norte. The methodology adopted consisted of an inventory of the local floristic composition. The plants were identified by means of specific literature, and the unidentified species were photographed and sent to specialists. The floristic list was classified based on the APG IV classification. It was found that 62,5% of the species are exotic, with a predominance of the species nim (Azadirachtaindica), with a percentage of 53%, and the botanical family Fabaceae, representing 20% of the inventoried families, besides the presence of tree species with drastic pruning, paved areas without afforestation, and an expressive number of seedlings. It is required, therefore, that priority be given to native species, in addition to the need to take into account the species and place of planting and maintenance of the afforestation as a whole in the planning.